Air to Soil Temperature Comparison: A Case Study for Tarnab, Pakistan - Amna Shafi; Aamir Khan (Indonesian Journal of Sustainable Agriculture and Environmental Sciences (IJSAES), 2025)
Background: The study of air-soil coupling is crucial for agricultural lands such as Tarnab since it provides valuable insights into microbial dynamics, soil ventilation, and the biogeochemical cycle. In addition to this, the floods of 2010 (which also affected the Tarnab) add more value to this work. Governing the air-soil coupling is mandatory for providing the vital oxygen for the roots. Aim: In this research, the regression equations linking the seasonal daily average air temperature and seasonal daily average soil temperature have been established for Tarnab. Methods: The data of daily maximum/minimum air temperature and soil temperatures (8 am/5 pm), which have been regularly recorded at the Agriculture Research Institute Tarnab from 1996 to 2023, have been used to find the regression. Results: The average maximum temperature correlates strongly with 5 pm soil temperature in MAM (R2=0.4453] and DJF (R2=0.4995) with 26.75(95% CI: 23.04, 30.77) and 14.28(95% CI: 7.30, 18.83) confidence intervals, respectively and n=28. The R2 for the SON is fairly strong for the relationship between maximum temperature and 5 pm soil temperature, as well as minimum temperature and soil temperature at 8 am, with values 0.1748 {25.96[95% CI: 20.83, 29.43]} and 0.2872 {19.11[95% CI: 14.78, 22.18]}, respectively. Conclusion: Air temperature has shown an influence on soil temperature, besides some irregular behaviour.